Conservative management of a dentigerous cyst by marsupialization treatment: Clinical insight and a case report - Nidhi Chhabra; Anuj Chhabra; Ruchi Mehta (Wolters Kluwer Medknow Publications, 2018)
The progression of inflammation from a nonvital deciduous predecessor tooth around an unerupted permanent tooth is one of the possible etiologic factors for the development of a dentigerous cyst. The article reports the management of an inflammatory dentigerous cyst in an 11-year-old male patient, associated with the germ of an unerupted permanent maxillary canine. The patient was treated by extraction of the left first and second deciduous molars under local anesthesia and marsupialization of the cystic cavity. The patient was followed for 18 months, and eruptions of the permanent canine, first and second premolars, and gradual reduction of the radiolucent area were observed periodically. In conclusion, with proper case selection, marsupialization might be a good treatment option for the conservative management of dentigerous cysts.